Efficacy and inflammatory levels (IL-6, IL-10) of adjuvant application of vitamin-A in the treatment of pediatric Mycoplasma pneumoniae pneumonia: a systematic review and meta-analysis - Cao, Limei; Lin, Mali; Sheng, Fang; Chen, Buqing; Hu, Chuanze (Frontiers in Pediatrics, 2024)
The purpose of this study is to evaluate the efficacy of Vitamin A (VitA) as an adjuvant therapy for pediatric Mycoplasma Pneumoniae Pneumonia (MPP) through meta-analysis, and to investigate its impact on inflammation levels (IL-6, IL-10), in order to explore the role of VitA in pediatric MPP. Methods: Using a systematic literature search method, relevant research literature is searched, and RCT studies that meet the requirements are selected based on preset inclusion and exclusion criteria. Then, a quality evaluation was conducted on the included literature, and meta-analysis was used to calculate the combined effect values of mortality rate, hospital stay, lung rale disappearance time, cough duration, fever duration, IL-6 and IL-10 levels, and heterogeneity analysis was conducted. The levels of IL-6 and IL-10 represent the inflammatory levels in pediatric MPP patients, and exploring their changes has significant implications for the anti-inflammatory effect of treatment. Results: A total of 10 RCT studies were included, with a total sample size of 1485, including 750 cases in the control group and 735 cases in the observation group. The meta-analysis results of this study showed that there was a significant difference in the total clinical efficacy of using VitA adjuvant therapy compared to the control group without VitA [OR=3.07, 95%CI=(2.81,4.27)], P<0.05. However, there was no significant difference in the adverse reaction rate between the use of VitA as an adjuvant therapy and the control without VitA [OR=1.17, 95%CI=(0.61,2.27)], P>0.05. At the same time, the hospitalization time [MSD=-0.86,95% CI=(-1.61, -0.21)], lung rale disappearance time [MSD=-0.78, 95%CI=(-1.19,-0.51)], cough duration [MSD=-1.07, 95%CI=(-1.41, -0.71)], and fever duration [MSD=-0.47, 95%CI=(-0.72, -0.23)] using VitA as an adjuvant treatment were obviously lower. In addition, the meta-analysis outcomes also showed that the use of VitA adjuvant therapy can significantly reduce IL-6 [MSD=-1.07, 95%CI=(-1.81, -0.27)] and IL-10 [MSD=-0.13, 95%CI=(-0.31,0.12)] levels. Conclusion: Based on the meta-analysis results, VitA adjuvant therapy can significantly improve the clinical symptoms of pediatric MPP patients, shorten hospitalization time, promote the disappearance of lung rales, and alleviate cough and fever symptoms. In addition, VitA adjuvant therapy can effectively reduce inflammation levels, indicating its potential role in inhibiting inflammatory responses.